A tool to improve the performance of multidisciplinary teams in cancer care. Issue 2 (31st May 2019) - Evans, Lynleigh; Donovan, Brendan; Liu, Yiren; Shaw, Tim; Harnett, Paul
Abstract : Introduction: While multidisciplinary teams (MDTs) are well established in many healthcare institutions, both how they function and their role in decision-making vary widely. This study adopted an innovative methodology to assess multidisciplinary team performance and engage teams in performance improvement strategies. Methods: The study comprised a survey to evaluate MDT members' perceptions of their team's performance before the implementation of the programme and annually thereafter, and a maturity matrix designed as a self-assessment tool. Each MDT used the matrix to collectively assess its performance and identify areas for improvement. Results: In the first cycle, 180 member surveys from 19 MDTs were completed. This provided insights into team members' perceptions of performance. 12 of these teams continued with the study and all 12 completed the matrix. Most teams rated themselves at level one or two (low) on a scale of five for most items. Conclusions: The MDT survey and maturity matrix have the potential to be useful for cancer care teams to identify their strengths and weaknesses and monitor performance over time and also for management to review its performance against standard criteria and to identify priority areas for improvement and further support.